The Role of Health Education: Changing Knowledge and Attitude of Adolescents in Providing Reproductive Health - Lenna Oktaviani; Linatul Mufarikhah; Sarah Hanifa; Omega DR Tahun (Postgraduate, University of Mataram, 2024)
Adolescence is a transitional phase towards adulthood, marked by sexual maturation and identity exploration. Reproductive health encompasses physical, mental, and social well-being. Sexual education, provided by both parents and schools, is crucial for preventing unwanted pregnancies, abortions, and sexually transmitted infections (STIs). This study examines the impact of sexual education on adolescents' knowledge and attitudes about reproductive health, focusing on high school students in Jakarta, Bekasi, and Pekalongan. Using an experimental method (one group pretest-posttest design) over three months (April-June 2024), the study involved 120 respondents who completed questionnaires. Data analysis included univariate health promotion analysis and bivariate analysis using the Wilcoxon Signed Rank Test. The results showed a significant influence of sexual education on changes in knowledge and attitudes, with a p-value of 0.000 (p < 0.05). These findings suggest that health education interventions effectively enhance students' understanding and attitudes, providing valuable insights for schools in preventing unwanted pregnancies, abortions, and STIs.